Maxim violation in pretty little liars TV series - Kartika Yulianti; Ambalegin Ambalegin (Politeknik Negeri Bali, 2021)
This research was conducted due to the importance of cooperative principle in daily conversation, as Grice’s theory explained about cooperative principle which has been divided into four maxims: 1) maxim of quantity, 2) maxim of quality, 3) maxim of relation, and 4) maxim of manner. These four maxims are the rules that have to be obeyed by the speakers and the interlocutors during interactions. This research is focusing on maxim of violation occurred in Pretty Little Liars TV Series. The method used in this analysis is descriptive qualitative. Objects of the research are the types of the violation and also the implied meaning behind the violation. This research used the observation method using non-participatory technique in collecting the data, and pragmatics identity method in analyzing the data. In presenting the data, this research used informal method. The result of this research found out that there were fifteen violations happened in Pretty Little Liars, all of the maxims are violated during this show. The violation of maxim relation was the most dominant violation.